ASPECTS OF SURGICAL TREATMENT OF GIANT ATHEROSCLEROTIC ABDOMINAL AORTIC ANEURYSMS - A. E. Zotikov; A. F. Kharazov; A. S. Kutovaya; E. G. Myl'tsev; D. A. Lavrent'ev; V. A. Kulbak; V. G. Aznaurov («REMEDIUM GROUP» Ltd., 2020)
The article deals with some aspects of surgical treatment of giant atherosclerotic abdominal aortic aneurysms. Giant aneurysms measuring more than 10 cm in diameter are an extremely rare disorder. A total of 33 observations of surgical treatment of patients with this disorder are described in the English language literature. This article provides epidemiology data based on the publications we studied. Clinical cases described in both domestic and foreign literature are presented and reviewed. A summary table has been created on the basis of the data, which provides comprehensive information on the experience accumulated over the given time in the treatment of gigantic aortic aneurysms. Over 600 surgeries for abdominal aortic aneurysms, of which nine interventions for gigantic aneurysms, have been performed in A.V.Vishnevsky National Medical Research Institute of Surgery. So far, this is the largest experience in surgery of gigantic aortic aneurysms accumulated in one institution. The article presents an analysis of literature data in the context of the results of our own observations. The aspects of choosing the surgical treatment method, the advantages and disadvantages of both open interventions and endovascular operations were considered in detail. The authors described in detail the features of the choice of surgical access, the technique for isolating the aneurysm neck with a detailed analysis of the further course of the operation. Extensive visual material is presented such as CT-, CT angiography scans, intraoperative photographs. The outcomes of interventions are analysed, the mortality rate of post-surgical treatment of giant aneurysms is 0%, there is no significant difference in morbidity in comparison with surgery of smaller aneurysms.